STATE OF THE CASTINGS PRODUCTION OF IRON-CARBON ALLOYS - A. P. Melnikov (Литьë и металлургия, 2009)
The production of castings of iron-carbon alloys is analyzed. It is shown that production of compound, thin walled and light weight constructions is being increased.